Brugada syndrome and reduced right ventricular outflow tract conduction reserve: a final common pathway? - Behr, Elijah R; Ben-Haim, Yael; Ackerman, Michael J; Krahn, Andrew D; Wilde, Arthur A M (European heart journal, 2021)
Brugada syndrome (BrS) was first described as a primary electrical disorder predisposing to the risk of sudden cardiac death and characterized by right precordial lead ST elevation. Early description of right ventricular structural abnormalities and of right ventricular outflow tract (RVOT) conduction delay in BrS patients set the stage for the current controversy over the pathophysiology underlying the syndrome: channelopathy or cardiomyopathy; repolarization or depolarization. This review examines the current understanding of the BrS substrate, its genetic and non-genetic basis, theories of pathophysiology, and the clinical implications thereof. We propose that the final common pathway for BrS could be viewed as a disease of 'reduced RVOT conduction reserve'.